열공성 뇌경색으로 한방병원에 입원한 환자의 자립생활에 영향을 미치는 인자에 대한 연구 - 박유진(Yu Jin Park); 이형권(Hyung Kwon Lee); 김기태(Ki Tae Kim); 고흥(Heung Ko) (동의생리병리학회지, 2012)
This study sought a clinical analysis of 43 lacunar infarction patients treated by oriental medical therapies. The patients were divided into two groups (independent living group and dependent living group) according to K-MBI independence level. We had analyzed correlation of many factors like past history, several symptoms of lacunar infarction and ect between independent living group and dependent living group. The male to the female ratio of patients diagnosed lacunar infarction was 1:1.39, female(58.1%) was more dominant than male. The most common age group was 8th decade. The most common past history was Heart disease and without heart disease patients are treated well. Without hemiparesis, cognitive disorder, dysphagia patients are treated well. Patients arrived hopital within 72 hours after onset had treated well In regard to K-MBI of lacunar infarction patients, 65.1% improved and no one got worse. After treatment, 74.4% patients were able to independent living. The correlation between herbal medication and improvement was not founded.